The study of Sabah Tourism Board (STB) information counter service quality / Caroline Sungkim - Sungkim, Caroline (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2006)
The service quality of an information counter focuses on the employees at the counter as they performed the service to the customers. In tourism industry, the total tourism experience is reflective to the processes utilize sources of tourist information to update existing knowledge and inform preparation for subsequent experiences. As for information counter service, the customers may not always happy with the quality and value of the services they receive. People may complain about rude or incompetent personnel, inconvenient service hours, poor performance, and needlessly complicated procedures. An easy access on this tourism product information is extremely important as this is the starting step to reach the point of sales of the tourism product. The information counter in travel agency is one of the main places that the tourists can come up to collect information about the attractive destination that they would like to visit. It is to give them a clearer picture of what to expect before they reach the destination that they wish to visit. Any information received by the tourist at information counter may construct the tourist's expectation and satisfaction on tourism product. The employees should have an in-depth knowledge about the tourism product. The front-liners should be able to solve the tourist's problems as they are the closets to the tourists. It is to fulfill the tourist's satisfaction in getting information at the information counter service.